Effects on vibrational energy, electronic and optical properties Of SiO2 glass incorporated with alumina / Radhiah Mohd Nor - Mohd Nor, Radhiah (2018)
SiO2 glass is one of the most used material in optical applications since it possess excellent properties such as exhibits ultra-low-optical loss of 0.2 dB/km at wavelength of 1.55 µm and highly transparent across a broad range of wavelengths. Doping of RE ion into SiO2 glass is necessary as an optical activator in SiO2-based devices. However, SiO2 glass suffers from high phonon energy, of about 1100 cm-1 that affects the emission of RE ion. Since SiO2 glass has high phonon energy and the RE ion itself has a non-radiative emission, thus photon emission has to compete with this vast amount of phonon. From the relationship of non-radiative decay rate, incorporating lower phonon energy material into SiO2 glass would change its phonon energy. Al2O3 is one of the favourable glass intermediate to be incorporated into SiO2 glass since it has lower phonon energy than SiO2 glass that is 780 cm-1 . However, the incorporation of Al2O3 in SiO2 glass will lead to phase separation if the amount of Al2O3 exceeds certain amount of ratio. Experimental works show variation in the molar ratio of SiO2- Al2O3 composition from 0 to 90% which are due to the different experimental techniques and initial treatments to the sample. Therefore, it is necessary to find the theoretical limit of SiO2-Al2O3 since there is no available work on finding the optimum ratio of SiO2-Al2O3 by theoretical approach. In this present work, small sample of SiO2 glass was successfully been generated using Rietveld refinement technique and calculated using density functional theory (DFT) framework. A thorough analysis on the properties of SiO2 glass structure are validated with previous works and serve as a reference to analyse the effect of Al2O3 on the vibrational, electronic and optical properties of SiO2 glass besides to determine the optimal composition of SiO2-Al2O3 system. The composition of Al2O3 has been limited to a desired amount so as not to perturb other properties of SiO2. The Infrared (IR) and Raman spectra for SiO2-Al2O3 systems were simulated at different molar ratio using Molecular Mechanics framework. It has been found that phonon energy of SiO2 glass has been reduced as the intensity of ~1091 cm- 1 band is reduced about 50 % with the proportion of 20 mol % Al2O3 in SiO2 host. The decreasing in intensity of ~1091 cm-1 band demonstrates the formation of Al-O-Si linkages in the structure. However, upon further addition of 50 mol % of Al2O3, the development of Al-O-Al bond can be observed which indicates the occurrence of phase separation phenomena. The structure also tends to exhibit similar electronic and optical properties with that pure SiO2 system.